Optimization of Storage Temperature for Cultured ARPE-19 Cells. (22nd October 2013) - Pasovic, Lara; Utheim, Tor Paaske; Maria, Rima; Lyberg, Torstein; Messelt, Edward B.; Aabel, Peder; Chen, Dong Feng; Chen, Xiangjun; Eidet, Jon Roger
Abstract : Purpose . The establishment of future retinal pigment epithelium (RPE) replacement therapy is partly dependent on the availability of tissue-engineered RPE cells, which may be enhanced by the development of suitable storage methods for RPE. This study investigates the effect of different storage temperatures on the viability, morphology, and phenotype of cultured RPE. Methods . ARPE-19 cells were cultured under standard conditions and stored in HEPES-buffered MEM at nine temperatures (4°C, 8°C, 12°C, 16°C, 20°C, 24°C, 28°C, 32°C, and 37°C) for seven days. Viability and phenotype were assessed by a microplate fluorometer and epifluorescence microscopy, while morphology was analyzed by scanning electron microscopy. Results . The percentage of viable cells preserved after storage was highest in the 16°C group (48.7 % ± 9.8 %; P < 0 . 01 compared to 4°C, 8°C, and 24°C–37°C; P < 0 . 05 compared to 12°C). Ultrastructure was best preserved at 12°C, 16°C, and 20°C. Expression of actin, ZO-1, PCNA, caspase-3, and RPE65 was maintained after storage at 16°C compared to control cells that were not stored. Conclusion . Out of nine temperatures tested between 4°C and 37°C, storage at 12°C, 16°C, and 20°C was optimal for maintenance of RPE cell viability, morphology, and phenotype. The preservation of RPE cells is critically dependent on storage temperature.